Antibacterial Activity of Biosynthesized Copper Oxide Nanoparticles (CuONPs) Using Ganoderma sessile - Karla M. Flores-Rábago; Daniel Rivera-Mendoza; Alfredo R. Vilchis-Nestor; Karla Juarez-Moreno; Ernestina Castro-Longoria (MDPI AG, 2023)
Copper oxide nanoparticles (CuONPs) were synthesized using an eco-friendly method and their antimicrobial and biocompatibility properties were determined. The supernatant and extract of the fungus Ganoderma sessile yielded small, quasi-spherical NPs with an average size of 4.5 ± 1.9 nm and 5.2 ± 2.1 nm, respectively. Nanoparticles were characterized by UV−Vis spectroscopy, transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), dynamic light scattering (DLS), and zeta potential analysis. CuONPs showed antimicrobial activity against Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Pseudomonas aeruginosa (P. aeruginosa). The half-maximal inhibitory concentration (IC50) for E. coli was 8.5 µg/mL, for P. aeruginosa was 4.1 µg/mL, and for S. aureus was 10.2 µg/mL. The ultrastructural analysis of bacteria exposed to CuONPs revealed the presence of small CuONPs all through the bacterial cells. Finally, the toxicity of CuONPs was analyzed in three mammalian cell lines: hepatocytes (AML-12), macrophages (RAW 264.7), and kidney (MDCK). Low concentrations (<15 µg/mL) of CuONPs-E were non-toxic to kidney cells and macrophages, and the hepatocytes were the most susceptible to CuONPs-S. The results obtained suggest that the CuONPs synthesized using the extract of the fungus G. sessile could be further evaluated for the treatment of superficial infectious diseases.